2009
DOI: 10.1007/s10072-009-0195-7
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and cerebral infarction in young people

Abstract: The objective of this study is to investigate relationship between migraine and cerebral infarction in young people. Patients aging 16-44 years, referred for stroke and age- and gender-matched controls were investigated for migraine following the International Headache Society criteria. Included people were 314 strokes and 314 controls. Each group consisted of 150 men and 164 women. Of the 105 persons with migraine (16.7%), 57 had migraine with aura (9.1%). In women, migraine with aura was related to stroke [3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Migraine may be a less-well documented and even controversial risk factor for stroke, but an association between migraine and stroke, especially in young patients, has indeed been shown in the literature [6,[20][21][22]. Quite a large percentage of our patients had a history of migraine (21%).…”
Section: Risk Factorsmentioning
confidence: 69%
“…Migraine may be a less-well documented and even controversial risk factor for stroke, but an association between migraine and stroke, especially in young patients, has indeed been shown in the literature [6,[20][21][22]. Quite a large percentage of our patients had a history of migraine (21%).…”
Section: Risk Factorsmentioning
confidence: 69%
“…Thus, the MIRACLES results add to the growing evidence that migraine is associated with increased risk of cerebrovascular events. Previously published studies reported an increased risk of stroke in young women with migraine [8,10,11,15,17,18]. In a meta-analysis of 14 observational studies, an increased risk of stroke in patients with migraine was found, with relative risk of 2.16 for migraine in general, 2.28 for migraine with aura, 1.56 for migraine without aura, and 2.76 for women younger than 45 years [12].…”
Section: Discussionmentioning
confidence: 89%
“…In fact, in recent decades, migraine, and specifically migraine with aura, has been associated with an increased risk of ischemic stroke [8][9][10][11][12][13][14][15][16][17][18], which is further increased by cigarette smoking and use of oral contraceptives [19].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have detected an increased risk for ischemic stroke in patients who had migraine with aura [1518]. Vasospasm emerging prior to or during the pain has been considered to occur concurrently in tissues located outside the brain, and, by extension, local infarctions have been considered to lead to histopathological and functional disorders at the tissue level.…”
Section: Discussionmentioning
confidence: 99%
“…Evidences from the literature suggest that there is a stronger vascular risk associated with MWA than with MWoA which focuses attention on the importance of the aura in vascular disease [1518]. We speculated that a putative vascular mechanism linking migraine and modification of posterior ocular structures is specifically referred to MWA.…”
Section: Discussionmentioning
confidence: 99%